Integrating communication and passing networks in football using social network analysis. Issue 1 (2nd January 2019) - Mclean, Scott; Salmon, Paul M; Gorman, Adam D; Dodd, Karl; Solomon, Colin
ABSTRACT: Background: Effective intra-team communication (ITC) is an important component for optimal team performance.Methods: In this study, an intra-team communication tool (ITCT) was used for players to report the amount of communication (ACOM) received, and the amount of perceived benefit to performance of that communication (BCOM). The ITCT was used to understand how a professional football team is connected, by ITC and passing, and the relationship between ITC and passing, using social network analysis (SNA).Results: The results indicated that the team was highly connected and cohesive for ITC, but less so for passing. In matches won compared to lost, passing connections were lower and ITC connections were higher. There were negative correlations between ITC and passing for the mean sociometric status values. For the SNA metrics, network edges were higher in matches won compared to drawn for BCOM. Cohesion was lower in drawn compared to won matches for BCOM, and lower compared to matches won and lost for passing. SMS was higher in matches won compared to lost for ACOM and BCOM, but was higher in matches lost compared to won for passing.Conclusions: The results could indicate that in matches when possession was increased, and ITC decreased, the team may coordinate implicitly, by relying on pre-existing knowledge of practiced playing structures. Whereas, in matches with low possession, increased levels of ITC may be required, due to the uncertainty associated with defending. However, further research is needed to confirm the current explanations of the results. This study has implications for the design of training practice.